PRESIDENT TRUMPS’ STRATEGY: CONTINUITY AND NEW APPROACHES - O. V. Prikhodko; P. Ye. Smirnov (Vestnik MGIMO-Universiteta)
After Donald Trump took office as President of the United States, Washington displays in many respects a new foreign policy philosophy, as well as non-conventional political practices. The 45th President has virtually resigned the liberal globalist paradigm, he is highly sсeptical about key transnational institutions of the world order, he would not hesitate to withdraw from key agreements signed by the United States if these agreements do not suit the current team in the White House. Trump’s national capitalism, his trade protectionist practices have caused a major crisis between the United States and its partners and allies, enhanced tensions with rival states.The authors of this article compare basic philosophic and doctrinal elements of Trump’s ‘grand strategy’ and major practical steps by his administration in the foreign and trade policies. The main conclusion from this analysis is that, despite Trump’s obvious abdication of the U.S. leadership in the liberal world order and its institutions, he is in no way isolationist within the world system. This applies to everyone who takes office as U.S. President, irrespectively of his/her political views. Donald Trump’s policies in 2017 and the first half of 2018 show that his America First rhetoric, his assurances of not seeking to impose the American way of life on anyone, do not contravene the use of force in conflicts in the U.S. interests, or widening the U.S. military presence abroad if Washington sees a threat to its vital strategic interests. This includes regions adjacent to the Russian frontiers. Power projection, as well as maintaining the U.S. - led security alliances – no matter how deeply they may be divided – is the key element of continuity in Washington’s strategy. Increased tensions in the U.S. – Russia and U.S. – China relations are inevitable in these circumstances, since the Trump administration declared them ‘revisionist powers’. Getting out of the deep crisis in the U.S. –Russian relationship becomes still more difficult and requires creativity and non-standard approaches.